Publication Update- Institute of Borneo Studies, UNIMAS Vol.1 March 2016 - Shahren, Ahmad Zaidi Adruce; Awang Azman, Awang Pawi; Lam Chee, Kheung; Langub, Jayl; Yusuf, Adibah; Suhaili, D.S; Stephen, Donald; John, Alexandra Nastassia (Universiti Malaysia Sarawak, (UNIMAS), 2015)
This is the first publication update aimed at highlighting the writings and studies that have been published either by the previous and present researchers of the Institute. There are three research chairs at the Institute of Borneo Studies, the Nusantara Chair, the Sino-Borneo Chair and also the Dayak chair.